2022
DOI: 10.1038/s41598-022-20732-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of cattle microbiota in different regions of Kazakhstan using 16S metabarcoding analysis

Abstract: Methane (CH4) is an important greenhouse gas (GHG). Enteric methane emissions from farmed ruminant livestock account for approximately 15% of global GHG emissions, with approximately 44% of livestock emissions in the form of methane. The purpose of the research is to study the influence of feeding types and regional characteristics of Kazakhstan on the microbiota of feces and the number of methane-forming archaea of beef and meat-and-dairy cattle productivity. For this purpose, fecal samples were taken rectall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…For this purpose, fecal samples were taken rectally from 37 cattle heads from 4 regions of Kazakhstan (Western, Southern, Northern, and Southeast Kazakhstan). As a result of the studies, it was found that methanogenic bacteria were less present in animals from the Western region grazing in the pasture compared with animals from other regions kept in the stall [22].…”
Section: Discussionmentioning
confidence: 95%
“…For this purpose, fecal samples were taken rectally from 37 cattle heads from 4 regions of Kazakhstan (Western, Southern, Northern, and Southeast Kazakhstan). As a result of the studies, it was found that methanogenic bacteria were less present in animals from the Western region grazing in the pasture compared with animals from other regions kept in the stall [22].…”
Section: Discussionmentioning
confidence: 95%
“…These innovative and powerful technologies are used in different fields for the detection of food frauds, identification of fish species or inspection of the dietary diversity of animals. However, bacteria are more frequently the target of the study, compared to parasites (20,(30)(31)(32)(33). For example, Ludwig, A. et al, and Howells et al described the presence of microorganisms such as parasites in the meat, but it was not possible for them to establish potential co-carriage, due to the technologies used, hence the interest of our study [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…These innovative and powerful technologies are used in different fields for the detection of food frauds, identification of fish species or inspection of the dietary diversity of animals. However, bacteria are more frequently the target of the study, compared to parasites [19,[31][32][33][34]. For example, Ludwig, A. et al, and Howells et al described the presence of microorganisms such as parasites in meat, but it was not possible for them to establish potential co-carriage, due to the technologies used, hence the interest of our study [5,8].…”
Section: Discussionmentioning
confidence: 99%